2006
DOI: 10.1271/bbb.60327
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization ofD-Galacturonic Acid Reductase, a Key Enzyme of the Ascorbate Biosynthesis Pathway, fromEuglena gracilis

Abstract: D-Galacturonic acid reductase, a key enzyme in ascorbate biosynthesis, was purified to homogeneity from Euglena gracilis. The enzyme was a monomer with a molecular mass of 38-39 kDa, as judged by SDS-PAGE and gel filtration. Apparently it utilized NADPH with a Km value of 62.5+/-4.5 microM and uronic acids, such as D-galacturonic acid (Km=3.79+/-0.5 mM) and D-glucuronic acid (Km=4.67+/-0.6 mM). It failed to catalyze the reverse reaction with L-galactonic acid and NADP(+). The optimal pH for the reduction of D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…On the other hand, Euglena ALase showed redox sensitivity caused by H 2 O 2 treatment (Table 3). Activation of D-GalUA reductase by H 2 O 2 has also been observed in our previous study (21). Because AsA levels in Euglena cells increased under oxidative stress (20,27) and light (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…On the other hand, Euglena ALase showed redox sensitivity caused by H 2 O 2 treatment (Table 3). Activation of D-GalUA reductase by H 2 O 2 has also been observed in our previous study (21). Because AsA levels in Euglena cells increased under oxidative stress (20,27) and light (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…This result provides compelling evidence that ALase is essential for AsA biosynthesis, and the pathway via uronic acid is the major source of AsA in Euglena cells. We previously reported that a D-GalUA reductase purified from Euglena had almost the same catalytic efficiency with two uronic acids, D-GalUA and D-GlcUA (21). Judging from the enzymology parameters of both D-GalUA reductase and ALase, it is difficult to understand which is the more effective route to promote the level of AsA in Euglena cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pathway actually operates in the unicellular alga Euglena gracilis. 25,26) On the other hand, the product of the myo-inositol oxygenase reaction is presumably a D-glucuronate, assuming the occurrence of the AsA biosynthetic pathway in higher plants, similarly to animals. In the cases of both alternative L-gulose and D-glucuronate pathways, to generate AsA, the presence of L-gulono-1,4-lactone (L-GulL) oxidase or dehydrogenase is essential to complete them.…”
Section: Ascorbate Biosynthesis In Photosynthesizing Organismsmentioning
confidence: 99%